Design of microwave ceramic waveguide filter with high out-of-band suppression characteristics - Fei LIANG; Shunliang MENG; Wenzhong LYU (Tongxin xuebao)
The design theory of ceramic waveguide filter was introduced, and then the combination structure of coupling through slot with shallow or deep coupling blind hole was designed, which could meet the requirements of positive and negative coupling bandwidth.By adjusting the cross coupling between 3～6 cavities, the symmetry of the filter transmis-sion curve was improved, and the near and far end band suppression of the filter was realized.Finally, a six-cavity ce-ramic waveguide filter for 5G base station was designed.In the process of optimizing the filter, the influences of the rela-tive position offset of the cross-coupling through slot and the length of the cross-coupling through slot on the transmis-sion zero position, the near end and far end out of band suppression characteristics of the filter were discussed in detail, and the relevant change rules were given.The performance indexes of the optimized filter were as follows, center fre-quency was 3.5 GHz, working bandwidth was 200 MHz, insertion loss ≤ 1.2 dB, return loss ≥ 17 dB, near end out of band rejection ≥ 25 dB, far end out of band rejection ≥ 51 dB.According to the structural parameters of the simulation model, the performance test results of the samples are in good agreement with the simulation results.